Anatase TiO2 Confined in Carbon Nanopores for High‐Energy Li‐Ion Hybrid Supercapacitors Operating at High Rates and Subzero Temperatures. Issue 2 (19th November 2019) - Fu, Wenbin; Zhao, Enbo; Ma, Ruiying; Sun, Zifei; Yang, Yang; Sevilla, Marta; Fuertes, Antonio B.; Magasinski, Alexandre; Yushin, Gleb
Abstract: Li‐ion hybrid supercapacitors (Li‐HSCs) hold great promise in future electrical energy storage due to their relatively high power and energy density. However, a major challenge lies in the slow kinetics of Li‐ion intercalation/extraction within metal‐oxide electrodes. Here, it is shown that ultrafast charge storage is realized by confining anatase TiO2 nanoparticles in carbon nanopores to enable a high‐rate anode for Li‐HSCs. The porous carbon with interconnected pore walls and open channels not only works as a conductive host to protect TiO2 from structural degradation but also provides fast pathways for ion/electron transport. As a result, the assembled cells exhibit remarkable rate capabilities with a specific capacity of ≈140 mAh g −1 at a slow charge and ≈60 mAh g −1 at a 3.5 s fast charge. While the charge/discharge process can be completed as fast as that of state‐of‐the‐art electrical double‐layer capacitors (EDLCs), the produced nanocomposites show three to seven times higher volumetric capacitance than activated carbons used in commercial EDLCs with acetonitrile‐based electrolytes. Equally important for some applications in cold climates or the space, the Li‐HSCs can operate at subzero temperatures as low as −40 °C, which is likely only limited by thermal properties of the acetonitrile (melting point of −45 °C). Abstract : The confinement of anatase TiO2 in conductive carbon nanopores can be an effective strategy to promote the rate capability of Li‐ion hybrid supercapacitors. Significant structural advantages of the produced nanocomposites are demonstrated. The assembled cells based on the nanocomposites can operate at ultrahigh rates and subzero temperatures.